Inhibitory effect of edible films and coatings containing selected amino acids on the formation of 2-amino-1-methyl-6-phenylimidazo[4-5-b]pyridine (PhIP) in pan-fried chicken breasts - Farshi, Parastou (Kansas State University, 2022)
This study was conducted to investigate the inhibitory effects of edible films and coatings containing amino acids (AAs) on the formation of 2-amino-1-methyl-6-phenylimidazo [4,5-b] pyridine (PhIP) in chicken breasts and to evaluate the physicochemical properties of the chicken. Heated whey protein isolate (HWPI) solution (100g ) was made by heating 5 g whey protein isolate (WPI) solution at 90 ºC for 30 min (in a water bath). After cooling down the solution, it was mixed with 2.5 g glycerol (GLY), and tryptophan (Trp) or lysine (Lys) were added at 0.25%, 0.5%, and 0.75% (w/w of the coating solution) concentrations, subsequently. Unheated whey protein isolate (UHWPI)-based casting solution was prepared with the same method but without heating of WPI solution. Chicken breasts were cut were covered with the prepared edible films and pan-fried at 195 ºC for 7.5 min on each side using an electrical frying pan with adjustable heat. The average PhIP level decreased from 78.47 ppb to 6.69-8.31 ppb for chicken covered with Lys containing HWPI edible films, and to 16.09-46.80 ppb for chicken covered with Trp containing ones. For chicken covered with UHWPI edible films the PhIP decreased to 7.75-40.32 ppb for Lys containing ones and to 28.4-56.04 ppb for Trp containing ones. Moreover, chicken breasts covered with HWPI edible films had lower cooking loss and improved tenderness compared to the chicken breasts with no edible film. Furthermore, the effect of potato starch (PS) coating containing AAs on the formation of PhIP in chicken breasts was studied, and physicochemical properties of chicken were evaluated. The PS coating solution (100 g) was made by heating 5 g of PS in water solution at 80 ºC for 30 min (in a water bath). After cooling down, GLY (2 g/100 g w/w of PS), and Trp or Lys were added to the solution at 0.25%, 0.5%, and 0.75% (w/w of the coating solution). Chicken breasts cuts were dipped in the PS coating solution for 15 min before frying. Chicken coated with PS with no AA and chicken with no coating were used for comparison. After frying the chicken at 195 ºC for 7.5 min on each side, PhIP level, color, cooking loss percentage, tenderness, and texture profile, viscosity of the PS coating solution and coating pickup percentage by chicken were measured. Triangle test was also conducted for consumer discrimination. The average PhIP concentration was decreased from 92.62 ppb for the control chicken breast without coating to 6.30 ppb (0.25% Lys), 6.76 ppb (0.5% Lys), and 11.98 ppb (0.75% Lys), respectively accounting for a 89%-92% reduction in PhIP level compared to the chicken breast without coating. However, dipping in Trp containing PS coating had significantly lower (p<0.05) PhIP reduction effect (34-67%). Moreover, there was not a significant difference (p>0.05) in cooking loss percentage, tenderness, texture profile parameters, color parameters of PS coated chicken compared to the chicken breasts with no coating, after frying. Triangle test results showed that consumers cannot find a significant difference between the PS coated and uncoated chicken breasts at (p<0.001). PS-0.25% Lys coating solution was selected to evaluate the effect of dipping time of chicken breast on the formation of PhIP and its possible inhibitory mechanism. Lys (0.25% w/w of solution) was added to the gelatinized 5% (w/w) PS solution. The chicken breasts with the same dimensions were dipped in the coating solution for different times (15 min, 30 min, 1 h, 3 h, and 6 h) and after draining the excess coating chicken were kept under hood for 20 min to dry the coating on them. Chickens were subsequently pan-fried at 195 ºC for 7.5 min (on each side). The PhIP level, tenderness, texture profile, color and cooking loss were evaluated for chicken breasts after pan-frying. Phenylacetaldehyde (PheAce), and volatile compounds were also determined using GC-MS for a selected samples. Chicken with no coating was used for comparison. Results showed that dipping time does not significantly decrease (p>0.05) the PhIP level suggesting that 15 min dipping time is enough for PhIP reduction compared to the control chicken without coating. Moreover, phenylacetaldehyde (PheAce) was shown to increase in chicken breast coated with PS-0.25% Lys, suggesting that there should be another pathway to prevent PhIP by PS-0.25% Lys. Volatile compounds analysis showed an increase in several aroma compounds such as pyrazines in the coated chicken. Moreover, no significant differences (p>0.05) was shown between cooking loss percentage, color parameters, texture profile and tenderness of chicken with PS-0.25% coating and chicken without coating. Overall, the results of this study suggested that application of edible films and coatings containing Lys and Trp to chicken breasts could effectively mitigate the PhIP formation during cooking.
Keywords: Edible films; Coatings; Lysine; Tryptophan; PhIP; Chicken breast